Ibrutinib as a salvage therapy after allogeneic HCT for chronic lymphocytic leukemia - Michallet, Mauricette; Dreger, Peter; Sobh, Mohamad; Koster, Linda; Hoek, Jennifer; Boumendil, Ariane; Scheid, Christof; Fox, Christopher P.; Wulf, Gerald; Krüger, William; Gelder, Michel van; Corradini, Paolo; et al. (Bone marrow transplantation, 2020)
The purpose of our study is to provide information on safety and efficacy of ibrutinib as salvage treatment after allo-HSCT for CLL. A total of 56 patients were included, 36 (64%) males; median age at transplantation was 48 years (range: 35-64) and the median number of treatment lines prior to transplantation was 3 (1-10). The median time between allo-HSCT and Ibrutinib was 30 months (range: 1-140). Overall, 40 (71%) patients responded to Ibrutinib; 23 (41%) PR, and 17 (30%) CR. At time of ibrutinib initiation, ten patients had active chronic GVHD that resolved under Ibrutinib, whilst a single patient developed limited de novo chronic GVHD on Ibrutinib. Fourteen patients discontinued ibrutinib, four because of toxicity and ten because of disease progression. Overall, 14 patients progressed (median PFS = 24 months) among them 10 died. Two-year OS and PFS probabilities were 72% (95% CI: 52-84) and 50% (95% CI: 32-66), respectively. Patients with late relapse after allo-HSCT (≥24 months) had a better PFS after ibrutinib. Our study shows that ibrutinib can be safely administered for CLL relapse after allo-HSCT, with comparable efficacy to non-transplanted patients with high-risk disease.
Published online: 7 November 2019
Gesehen am 29.09.2020